Infarction in the territory of the medial branch of the posterior inferior cerebellar artery. - Amarenco, P (1990)
We report 10 cases of cerebellar infarction in the territory of the medial branch of the posterior inferior cerebellar artery (mPICA). Axial sections on MRI through the middle of the medulla and the cerebellum showed the infarction as a triangular area with a dorsal base and a ventral apex directed towards the fourth ventricle. The infarct also involved the lateral and dorsal medulla when the mPICA supplied all or part of these regions. Three clinical patterns were observed: 1) pseudolabyrinthine signs with or without dysmetria and ataxia when the medulla was spared; marked axial lateropulsion was present in most cases; 2) complete or incomplete Wallenberg's syndrome, when the medulla was involved; 3) silent infarction. These syndromes are precisely those previously attributed to PICA occlusion without distinction of the branch involved. No alteration of consciousness was recorded and spontaneous recovery was the rule. Cerebellar infarction in the distribution of the mPICA can be regarded as a benign condition with a good prognosis.